Rare cause of colonic intussusception in an adult - Nissen, Alexander (BMJ Case Rep, 2017)
Colonic intussusception is an uncommon phenomenon in adults. Advanced imaging has facilitated the increase in awareness of this rare disease. When present, the lead point is most often secondary to a malignancy with primary adenocarcinoma being the most frequent cause. Current surgical management involves oncologic resections for this reason. This is a report of the third ever-reported case of colonic intussusception secondary to an angiolipoma and the first in the western hemisphere. We also demonstrate that these masses are amenable to minimally invasive resection for definitive management.